Akibat Hukum Konversi Hak Atas Tanah Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah - I Made Setiana Sanjaya; I Putu Gede Seputra; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
The land registration process requires certainty of the physical data of the land object as well as the certainty of the juridical data of the land subject as well as the party that provides information on the truth of ownership of the land. Participation will be realized if the community has an understanding of the greater benefit value if the land is registered and certified. The formulation of the research problems include: how is the regulation of conversion of land rights and what is the consequence of the law of land rights conversion. The type of research is research normative. The conclusions of this research include: Regulation of land rights conversion, among others, Law no. 5 of 1960 was promulgated on September 24, 1960, which marked the formation of the National Land Law. The legal consequences of land rights conversion include: having a legal title to land, with proof of certificate, there is a legal basis for ownership when a case / dispute occurs over the land and can be used as collateral / collateral at the Bank.